Experiência Interativa em 3D para Exibição de Animais Extintos no Museu Emílio Goeldi: Uma Abordagem Educacional e Tecnológica Baseada em WebGL - Pina, Israel Coimbra de; Souza, Tobias Moraes de; Silva Filho, Frederico Guilherme Santana da; Seruffo, Marcos Cesar da Rocha; Cardoso, Diego Lisboa (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2025: Proceedings of the 31st Brazilian Symposium on Multimedia and the WebDO - 10.5753/webmedia.2025.16163, 2025)
This work investigates the educational impact of an interactive web application based on WebGL for displaying three-dimensional models of extinct animals from Brazilian territory, applied to the Emílio Goeldi Museum context. The research addresses how interactive 3D visualization enhances visitor engagement and knowledge retention compared to traditional exhibitions. The methodology involved implementing advanced 3D model optimization techniques, responsive design, and intuitive interaction interfaces, ensuring accessibility across various devices. Five extinct Brazilian animals were selected as case studies: Megalonyx jeffersonii, Toxodon, Gomphotherium, Phorusrhacidae, and Glyptodon. The application was developed using React Three Fiber integrated with performance optimization libraries for mobile devices. A quasi-experimental study with 150 participants evaluated usability, engagement, and educational outcomes. Results demonstrated significantly higher engagement and knowledge retention. The research contributes to digital museology by demonstrating educational effectiveness, offering a replicable framework for museum institutions.